Homozygous GRID2 missense mutation predicts a shift in the D-serine binding domain of GluD2 in a case with generalized brain atrophy and unusual clinical features - Zafar Ali; Shumaila Zulfiqar; Joakim Klar; Johan Wikström; Farid Ullah; Ayaz Khan; Uzma Abdullah; Shahid Baig; Niklas Dahl (BMC, 2017)
Abstract Background Spinocerebellar ataxias comprise a large and heterogeneous group of disorders that may present with isolated ataxia, or ataxia in combination with other neurologic or non-neurologic symptoms. Monoallelic or biallelic GRID2 mutations were recently reported in rare cases with cerebellar syndrome and variable degree of ataxia, ocular symptoms, hypotonia and developmental delay. Case presentation We report on a consanguineous family with autosomal recessive childhood onset of slowly progressive cerebellar ataxia and delayed psychomotor development in three siblings. MRI of an adult and affected family member revealed slightly widened cerebral and cerebellar sulci, suggesting generalized brain atrophy, and mild cerebellar atrophy. Using whole exome sequencing we identified a novel homozygous missense variant [c.2128C > T, p.(Arg710Trp)] in GRID2 that segregates with the disease. The missense variant is located in a conserved region encoding the extracellular serine-binding domain of the GluD2 protein and predicts a change in conformation of the protein. Conclusion The widespread supratentorial brain abnormalities, absence of oculomotor symptoms, increased peripheral muscle tone and the novel missense mutation add to the clinical and genetic variability in GRID2 associated cerebellar syndrome. The neuroradiological findings in our family indicate a generalized neurodegenerative process to be taken into account in other families segregating complex clinical features and GRID2 mutations.